Mild Persistent Isolated Hypermethioninemia Identified through Newborn Screening in Michigan - Sen, Kuntal; Felice, Michael D.; Bannick, Allison; Colombo, Roberto; Conway, Robert L. (Journal of Pediatric Genetics, 2019)
Methionine S-adenosyltransferase deficiency, due to mutations in MAT1A, is the most common cause of persistent isolated hypermethioninemia (PIH). While the recessive form may cause neurological consequences, the dominant form is typically benign. This condition may be found in asymptomatic infants through newborn screening programs. We describe 16 asymptomatic individuals with PIH. Our data reiterates the benign nature of PIH and reports two novel mutations in the gene. There were a disproportionate number of individuals with African descent in this cohort.
Keywords: newborn screening; persistent isolated hypermethioninemia; MAT1A mutation